Nepenthes rafflesiana pitcher liquid has antifungal activity against Candida spp. - Hanna Yolanda; Ingrid M. Makahinda; Maureen Aprilia; Nikki Sanjaya; Harry Gunawan; Rita Dewi (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDTo develop new effective antifungals, it is essential to search for antifungal compounds from plants such as Nepenthes spp., which have their greatest diversity in Indonesia. Since chitin-induced liquid (CIL) from Nepenthes khasiana pitchers has antifungal activity, due to their naphthoquinone content, this study aimed to evaluate antifungal activity of Nepenthes rafflesiana pitcher liquids on Candida spp.METHODSCollected pitcher liquids were of 3 types: non-induced liquid (NIL), prey-induced liquid (PIL), and chitin-induced liquid (CIL). Non-induced liquid (NIL) was collected from fresh naturally opened pitchers, PIL from opened pitchers after 3 hours of induction with Zophobas morio larvae, and CIL from closed pitchers after 5 days of chitin solution injection. The antifungal activity of the liquids against C. albicans, C. glabrata, C. krusei, and C. tropicalis were detected by disc diffusion and macrodilution methods.RESULTSInhibition zone diameters of NIL, PIL, and CIL against C. albicans were 35.00 (35.00 – 39.33) mm, 26.33 (23.00 – 40.00) mm, and 30.00 ( 28.00 – 32.00) mm, respectively, while for C. glabrata the zone diameters were 22.22 ± 3.66 mm, 29.89 ± 2.79 mm, and 28.89 ± 1.17 mm, respectively. No inhibition zones were found for NIL, PIL, and CIL against C. krusei and C. tropicalis. At concentrations of 80%, almost all samples showed visually apparent inhibition of fungal growth.CONCLUSIONThe pitcher liquid of N. rafflesiana has antifungal properties, presumably due to the presence of many potentially active substances, such as naphthoquinones, as has been proven in other studies.